P-220 Ice crystals propagation velocity is related to the type and concentration of cryoprotectants and impacts cells and tissue vitrification success. (30th June 2022) - Patrizio, P; Natan, Y; Arav, R; Arav, A
Abstract: Study question: How different cryoprotectants at various concentrations affect ice crystals formation and propagation during vitrification? Summary answer: The velocity of ice crystal propagation is inversely related to concentration and type of cryoprotectants and is responsible for downstream cell damage during vitrification. What is known already: Vitrification has replaced slow freezing for oocyte and embryo cryopreservation and is now being considered also for gonadal tissue. However, the results in terms of both vitrification and rewarming survival rates are still not uniform. Understanding the complex physical events controlling ice crystals formation, propagation and expansion are key for improving cryoprotectant solutions and overcoming challenges. Study design, size, duration: Basic science research. Ice crystal propagation velocity was measured in solutions of four cryoprotectants: dimethyl sulfoxide (DMSO), propylene glycol (PG), ethylene glycol (EG) and glycerol (Gly), at various concentrations in supercooled temperatures. Each experiment used five 0.25ml and five 2ml straws (volume 0.1 ml and 1 ml) containing different cryoprotectant combinations (DMSO:EG, EG:PG, DSMO:PG, DMSO:Gly, EG:Gly, PG:Gly and EG+PG vs EG+DMSO), immersed in alcohol baths prepared at 8-10 °C below the freezing points of each solution. Participants/materials, setting, methods: Alcohol baths were set as follows: (1) between -10 °C and -12 °C for straws with 0% and 10% (v/v) DMSO, EG, PG and Gly; (2) -15 °C to -19 °C for the 20%; (3) -19.5 to -24 °C for the 30%, and for the mixture of 15% EG and 15% PG and 15% EG and 15% DMSO (most used vitrification solutions); and (4) -25 to -36 °C for the 40%. A 50µm thermocouple measured supercooling. Student's T-test analyzed differences. Main results and the role of chance: Seeding was done by touching the straw end with LN- precooled forceps until visualizing a small ice crystal. Following 10 to 60s the distance to which the ice crystals grew inside the straws was evaluated using a fine caliber. Ice crystal propagation was inversely correlated to type and cryoprotectant concentrations. Propylene glycol showed statistically significant lower ice crystals growth velocity up to concentrations of 30% (v/v), compared to DMSO and EG at the same concentrations (p < 0.05). Moreover, the ice crystal velocity of PG was also lower than Gly at these same concentrations. The combination of EG with PG decreased ice crystal propagation better than EG with DMSO. At concentrations of 40%, there were no differences. These results suggest that current cryopreservation vitrification solutions are not optimized and combining PG with other CPs has advantages. Using a vitrification solution of 40% DMSO or EG, the velocity of crystal growth was in the range of 0.1mm/sec (6mm/min). This means that to vitrify large tissues, a cooling rate of over 1000 °C/min from RT to a temperature of -196 °C (ΔT of 220 °C in 13 seconds) is necessary to avoid a single ice nucleus to grow to a size of 1.3mm during cooling or warming. Limitations, reasons for caution: Assessing the velocity of ice propagation is a novel concept to perfect vitrification/warming solutions. Wider implications of the findings: These results pave the way to develop protocols and platforms able to minimize the deleterious impact of cryoprotectant concentrations on both cells and tissues survival after vitrification. Trial registration number: not applicable